Etymology of the Legal-Canonical, Medical and Theological Terms Used in the Edict of the General Vicar of the Catania Diocese Concerning the Caesarean Section and Bridal Blessing by Vincenzo Maria Paterno’ - Artur Katolo (Kościół i Prawo, 2019)
Etymologia terminów kanoniczno-prawniczych, medycznych i teologicznych w Edict of the General Vicar of the Catania Diocese Concerning the Caesarean Section and Bridal Blessing  autorstwa Vincenzo Maria Paterno’